Galectin‐3 as Adjunct to HBME‐1 Staining of Fine‐Needle Aspiration Biopsy Samples of Thyroid Nodules. (2nd September 2014) - Scheffler, Patrick; Forest, Veronique‐Isabelle; Florea, Anca; Tamilia, Michael; Hier, Michael P.; Mlynarek, Alex M.; J Payne, Richard
Abstract : Objectives: (1) Examine the added value of galectin‐3 to HBME‐1 staining on fine‐needle aspiration (FNA) of thyroid nodules. (2) Correlate galectin‐3 on FNA with pathology results both on FNA and final surgical pathology. Methods: A retrospective review of the charts of 53 patients undergoing FNA at the Jewish General Hospital in Montreal, Canada, in 2013 for the investigation of thyroid nodules whose FNA samples underwent HBME‐1 and galectin‐3 staining in addition to pathological examination. Results: Of 53 FNABs, 20 (37%) were galectin‐3 positive, 24 (45%) were galectin‐3 negative, and 9 (17%) were equivocal. With regard to HBME‐1, 15 (28%) samples were positive, 32 (60%) were negative, and 6 (11%) were equivocal. Both stains correlated strongly with each other ( P <. 001) as well as with pathologist examinations of the FNA samples ( P <. 001 for both galectin‐3 and HBME‐1). Eleven patients underwent total or partial thyroidectomy. In correlation with surgical pathology, galectin‐3 was correctly positive in 5 patients, correctly negative once, falsely positive once, falsely negative once, and indeterminate in 3 patients. HBME‐1 was correctly positive in 7 patients, correctly negative in 2 patients, falsely negative once, indeterminate once, and without false positives. When combining HBME‐1 and galectin‐3, 8 true positives, 1 true negative, and 1 false positive were observed. No false negatives were found when combining both stains. Conclusions: Galectin‐3 may be a useful adjunct to HBME‐1 staining in FNA of thyroid nodules in order to detect papillary thyroid carcinoma. Further research is needed to confirm these results.